2021
DOI: 10.1177/10482911211039880
|View full text |Cite
|
Sign up to set email alerts
|

It Is Time to Implement Primary Prevention in the Workplace to Ameliorate the Ongoing U.S. Opioid Epidemic

Abstract: The United States’ opioid public health crisis continues having disastrous consequences on communities, including workers and employers. From May 2019 to May 2020, the largest number of drug overdose deaths was recorded over a twelve-month period. The “twindemics” of COVID-19 and opioids underscore the urgent need to address workers’ physical and mental health. Although much has been written about the negative impacts of the opioid epidemic on the workplace, few initiatives have focused on primary prevention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 34 38 The COVID-19 pandemic exacerbated the ongoing opioid epidemic and its interrelationship with psychological distress in the workplace, prompting calls for action from policy makers, business leaders, employers, and workers to take stock of how mental well-being is addressed in the workplace. 39 41 Though some employers may believe that workplace drug testing policies are net-beneficial to workplace well-being because they reduce physical hazards, such as drug-related workplace accidents and illnesses, 17 this study's findings indicate that such policies may simultaneously interact in harmful ways with psychological distress and are not universally associated with lower opioid misuse among workers. The net result of workplace drug policies may harm worker well-being more than they help.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“… 34 38 The COVID-19 pandemic exacerbated the ongoing opioid epidemic and its interrelationship with psychological distress in the workplace, prompting calls for action from policy makers, business leaders, employers, and workers to take stock of how mental well-being is addressed in the workplace. 39 41 Though some employers may believe that workplace drug testing policies are net-beneficial to workplace well-being because they reduce physical hazards, such as drug-related workplace accidents and illnesses, 17 this study's findings indicate that such policies may simultaneously interact in harmful ways with psychological distress and are not universally associated with lower opioid misuse among workers. The net result of workplace drug policies may harm worker well-being more than they help.…”
Section: Discussionmentioning
confidence: 60%
“… 56 , 57 From a primary prevention perspective, employers and professionals who oversee workplace health (e.g., industrial hygiene [IH] or occupational and environmental health and safety [OEHS] professionals) should conduct worksite ergonomics assessments to reduce the musculoskeletal disorders (MSDs) which may lead to chronic pain, opioid prescription, and potential opioid use/misuse disorders. 39 , 58 , 59 Robust primary prevention may include: establishing formal ergonomics programs to prevent musculoskeletal disorders; using administrative controls, such as scheduling, to limit workload so as to not overburden workers; and addressing negative psychosocial factors (e.g., low supervisor support, high job demands, low job autonomy) that research has demonstrated does indeed affect workers’ mental and physical health outcomes, especially in relation to musculoskeletal disorders incidence. 39 , 59 – 62 Workers’ compensation programs can make important contributions to secondary prevention by continuing to place limits on the quantity and circumstances under which providers can prescribe opioids and can require employers to shoulder the costs of nonpharmacological pain management approaches (e.g., physical therapy, acupuncture, massage therapy, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations